The Impact of Internal Party Splits on Political Identity The 1964 Split of the Kurdistan Democratic Party and Its Consequences as a Case Study - Shaheen, Dr. Nadia Salah Abdelshafi Mohamed (Sulaimani Journal for Humanities, 2025)
The significance of this study lies in shedding light on the internal split within the Kurdistan Democratic Party (KDP) in 1964 and examining the impact of this partisan split on the course of the Kurdish national liberation movement and Kurdish political identity. The study aims to uncover the causes and motives behind this split and to analyze the role played by the cultural and social differences among party members, as well as the influence of tribal sentiments and conflicting ideological visions on the party’s interests and the trajectory of the Kurdish movement. Relying on official documents, the study is structured around three main axes. The first axis provides a historical overview of the establishment of the Kurdistan Democratic Party and the stages it went through, from clandestine activity to open political engagement, followed by the transformation of part of its activities into an armed liberation movement after its political activities were banned by the Baghdad government. The second axis addresses the stages of disagreement and division within the party, examining their causes and development. The third axis analyzes the impact of this split on the Kurdish liberation movement and Kurdish political identity.
Keywords: Party Formation Establishment of the Party; Party Split Party Schism; Party Competition; Party Statement Party Manifesto